«Al aire» del to barroc. - JOSA, LOLA (Scripta, 2018)
The bucolic landscape became a kind of sheet music and metalyrical game in baroque tonos in such a way that it seems as if the performers and the voices that sing them have only to follow the indications that the poetic topics dictate from the text so that the sonority, harmony and music were possible. It is very curious also that, so belatedly, it was on the subject of pastoral-bucolic love the pretext with which the incipient art of the tono was more experimental. Only this musical motif could justify, that, at the beginning of the XVII century, the compositions of bucolic tonos proliferated and of those others that are centered in a Nature, although not idealized, not noticed by the later egocentric pantheism. In this work we will focus, therefore, on the causes of this effort of musical originality and its achievements, as well as the repercussion that it had on musicalized poetry. We will also follow the poetic-musical evolution of the bucolic-pastoral tono along with the best peninsular composers (some still unknown) to end up offering the most significant characteristics that allow us to fix it as one of the important typologies of the history of the peninsular music of the XVII century.